(untitled) (Fiep Bulletin - online, 2016)
Muay Thai is a combat that every day conquers more followers in Brazil. According to the many academies created and their masters confirm that this modality is beneficial to its practitioner. This study attempts to analyze what changes in the physical, educational and social aspects occurred in the students of the Federal University of Ceará, after participating in training combat MuayThai, provided by Focus Fights project. The project is developed in the Institute of Physical Education and Sports of the UFC, and has the support of Pro - Dean of Student Affairs - Prae and Pro - Deanship. For data analysis, questionnaires were administered to participants. The results showed significant percentages related to the proposed objectives. We conclude that the project is expected to corresponding expectations.